Climate crisis, gender inequalities and local response in Somalia/Somaliland - Croome, A; Hussein, M (Refugee Studies Centre, University of Oxford, 2020)
Various factors intersect when looking at the gendered effects of climate crisis on local communities in Somalia/Somaliland.